Effect of Organic Acids and Probiotics on Salmonella enteritidis Infection in Broiler Chickens - Wolfenden, A.D.; Vicente, J.L.; Higgins, J.P.; Filho, R.L. Andreatti; Higgins, S.E.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2007)
The effect of an organic acid mixture (OA) and a Lactobacillus-based probiotic culture on Salmonella enteritidis (SE) infection in broiler chicks was evaluated. In exp. 1, chicks were challenged by oral gavage with SE, held in chick boxes for 2 h and randomly assigned to either untreated control or continuous OA treatment in the drinking water. Crop and cecal tonsils were cultured at 48 h and 5 d post-challenge for recovery of SE. Recovery of SE in the crop and cecal tonsils at 48 h was significantly (p<0.05) lower in the OA treated group as compared to control chickens but not different at 5d. In exps.2 and 3, chicks were SE challenged, held in chick boxes for 2 h and randomly assigned to either untreated control, probiotic, OA, or probiotic+OA. After 24 or 48 h, crop and cecal tonsils were cultured for the presence or absence of SE. After 24 h, probiotic or probiotic+OA significantly reduced SE recovery from the crop as compared to controls. All treatments reduced SE recovery from the cecal tonsils at 24 h. While no significant differences were observed in SE recovery from crop at 48 h, SE recovery from probiotic and or probiotic+OA groups was significantly lower than the controls in the cecal tonsils. These data suggest that combination treatment with the selected OA and Lactobacillus-based probiotic culture is more effective than individual treatment for Salmonella reduction in chicks.